2022
DOI: 10.4196/kjpp.2022.26.6.511
|View full text |Cite
|
Sign up to set email alerts
|

Neogambogic acid relieves myocardial injury induced by sepsis via p38 MAPK/NF-κB pathway

Abstract: Sepsis-associated myocardial injury, an invertible myocardial depression, is a common complication of sepsis. Neogambogic acid is an active compound in garcinia and exerts anthelmintic, anti-inflammatory, and detoxification properties. The role of neogambogic acid in sepsis-associated myocardial injury was assessed. Firstly, mice were pretreated with neogambogic acid and then subjected to lipopolysaccharide treatment to induce sepsis. Results showed that lipopolysaccharide treatment induced up-regulation of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…signaling pathway can inhibit the cell cycle and cell apoptosis of lung cancer. A number of studies have been conducted on the PI3K-AKT-mTOR signaling pathway, which is an important pathway in signal transduction in cells, and it is closely related to the occurrence and development of lung cancer by in uencing the activation state of various effector molecules downstream (Fu et al 2022. Han et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…signaling pathway can inhibit the cell cycle and cell apoptosis of lung cancer. A number of studies have been conducted on the PI3K-AKT-mTOR signaling pathway, which is an important pathway in signal transduction in cells, and it is closely related to the occurrence and development of lung cancer by in uencing the activation state of various effector molecules downstream (Fu et al 2022. Han et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“… 55 Studies have concluded that the activated pro-inflammatory cytokines, oxidative stress and inflammation and C-reactive protein (CRP) are key mechanisms in the development of CVD. 56 Fu et al 57 evaluated the role of neoglycyrrhetinic acid in sepsis-associated myocardial injury, and they discovered that GNA exerts anti-apoptotic, anti-fibrotic and anti-inflammatory effects in septic mice through inactivation of the MAPK/NF-κB pathway. Studies have shown that GA can inhibit cardiac hypertrophy and fibrosis induced by pressure or isoprenaline infusion by inhibiting the NF-κB pathways and proteasome, indicating that GA therapy may a new strategy for the treatment of cardiac hypertrophy and fibrosis.…”
Section: The Role Of Caged Polyprenylated Xanthones In Diseasesmentioning
confidence: 99%
“…Recent research has shown that GNA ameliorates cardiac injury and dysfunction in LPS-induced septic mice by inhibiting cardiac apoptosis, fibrosis and inflammation through downregulation of p-JNK and p-NF-κB. 57 In a recent work, binding affinities of xanthone compounds which including morellic acid, gambogellic acid, GNA, moreollic acid with SARS-CoV-2 main protease (Mpro) were predicted using the molecular docking technique, the results showed that morellic acid has a high-binding affinity towards SARS-CoV-2 Mpro, and this suggests that MA is a promising candidate for anti-COVID-19; however, this requires further detailed in vivo experimental estimation and clinical evaluation. 64 …”
Section: The Role Of Caged Polyprenylated Xanthones In Diseasesmentioning
confidence: 99%
“…However, mitigating cardiomyocyte autophagy can attenuate sepsis-induced myocardial damage ( Yang et al, 2021 ). In a similar vein, cardiomyocyte apoptosis plays a significant role in the pathological cascade that culminates in myocardial injury during sepsis ( Fu et al, 2022 ). Nonetheless, evidence suggests that curbing cardiomyocyte apoptosis may offer therapeutic benefits in mitigating myocardial damage within the septic milieu ( Li et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%